The Mediating Role of Academic Self-Efficacy Between Gender and the Intention to Resume Schooling Among Depressed Adolescents: An Empirical Study from China - Ruiling Zhang; Chun Liu; Min Yang (Behavioral Sciences)
Depressed adolescents often face challenges in resuming schooling, with gender differences and psychological factors influencing their intentions. This study aimed to investigate the mediating role of academic self-efficacy in the relationship between gender and the intention to resume schooling. Using convenience sampling, 295 school-suspended depressed adolescents (aged 12–18; mean age 15.84 ± 1.49; 75 males, 220 females) completed the General Situation Questionnaire, Questionnaire on the Intention to Resume Schooling, Kutcher Adolescent Depression Scale, and Academic Self-efficacy Questionnaire. Data were analyzed via SPSS 27.0.1 and R 4.4.3 software. Mediation analysis was performed using logistic regression modeling. The results showed that 42.70% (126/295) of participants intended to resume schooling. Gender disparities emerged in both intention to resume schooling (χ2 = 18.63, p < 0.001) and academic self-efficacy (Z = 2.31, p < 0.001) among depressed adolescents. Additionally, academic self-efficacy significantly differed across intention to resume schooling (Z = 3.05, p < 0.001). Gender differences in resumption intention were partially mediated by academic self-efficacy (effect = −0.18, 42.86% of total effect), with a direct gender effect of −0.24 (57.14%). These findings suggest that the gender of depressed adolescents not only directly affects their intention to resume schooling, but also indirectly affects their intention to resume schooling through academic self-efficacy.